KONTROL RUANG PADA MASA PANDEMI COVID-19 - Manurung, Parmonangan (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2023)
The COVID-19 pandemic has changed human relations with the environment and with other space users. Control plays an important role in controlling human behavior and overseeing territorial space during the pandemic is an interesting study. Control aims to oversee the space from user intrusion that has the potential to endanger space territory, personal space, and privacy. The research was conducted using content analysis method. The research analyzes various published scientific articles related to research problems. The study found some shifts in space control during the pandemic, both from the purposes and methods used. The pandemic on the other hand also affects personal space and privacy due to user concerns about the potential for virus infection. There has also been a shift in the personal space due to fears of being infected by the virus. Based on research in various works of literature, the shift in space control is due to increased surveillance of users who have the potential to spread the virus.